WRKY41 controls Arabidopsis seed dormancy via direct regulation of ABI3 transcript levels not downstream of ABA. (28th July 2014) - Ding, Zhong Jie; Yan, Jing Ying; Li, Gui Xin; Wu, Zhong Chang; Zhang, Shu Qun; Zheng, Shao Jian
Summary Although seed dormancy is an important agronomic trait, its molecular basis is poorly understood. ABSCISIC ACID INSENSITIVE 3 (ABI3) plays an essential role in the establishment of seed dormancy. Here, we show that the lack of a seed‐expressed WRKY transcription factor, WRKY41, confers reduced primary seed dormancy and thermoinhibition, phenotypes resembling those for a lack of ABI3. Loss‐of‐function abi3‐17 and wrky41 alleles also both confer reduced sensitivity to ABA during germination and early seedling growth. Absence of WRKY41 decreases ABI3 transcript abundance in maturing and imbibed seeds, whereas transgenically overexpressing WRKY41 increases ABI3 expression. Moreover, transgenic overexpression of ABI3 completely restores seed dormancy phenotypes on wrky41. ChIP‐qPCR and EMSA reveal that WRKY41 binds directly to the ABI3 promoter through three adjacent W–boxes, and a transactivation assay indicates that these W–boxes are essential for ABI3 expression. Whilst RT‐qPCR analysis shows that the regulation of ABI3 by WRKY41 is not through ABA and other factors known to promote ABI3 transcription during seed maturation and germination, we also show that high concentrations of ABA might promote negative feedback regulation of WRKY41 expression. Finally, analysis of the wrky41 aba2 double mutant confirms that WRKY41 and ABA collaboratively regulate ABI3 expression and seed dormancy. In summary, our results demonstrate that WRKY41 is an important regulator of ABI3 expression, and hence of seed dormancy.